Macrophage Autophagy and Bacterial Infections - Bah, Aïcha; Vergne, Isabelle (Frontiers in Immunology, 2017)
Autophagy is a well-conserved lysosomal degradation pathway that plays key roles in bacterial infection. One of the most studied is probably xenophagy, the selective capture and degradation of intracellular bacteria by lysosomes. However, the impact of autophagy goes beyond xenophagy and involves intensive cross-talks with other host defense mechanisms. In addition, autophagy machinery can have non-canonical functions such as LC3-associated phagocytosis. In this review, we intend to summarize the current knowledge on the many functions of autophagy proteins in cell defenses with a focus on bacteria-macrophage interaction. We also present the strategies developed by pathogens to evade or to exploit this machinery in order to establish a successful infection. Finally, we discuss the opportunities and challenges of autophagy manipulation in improving therapeutics and vaccines against bacterial pathogens.